Live Imaging and Quantification of Neutrophil Extracellular Trap Formation. Issue 7 (14th July 2021) - Silva, Lakmali Munasinghage; Moutsopoulos, Niki; Bugge, Thomas H.; Doyle, Andrew
Abstract: N eutrophilE xtracellular T rap (NET) formation (NETosis) is a unique process that occurs in response to numerous stimuli. To investigate NETosis, we created a method that can be used easily without the need for complex programming abilities and commercial software packages. This article describes a fully automated assay to quantify NETosis using fluorescence live imaging on an automated widefield inverted microscope. Herein, we describe (1) sample preparation, (2) required equipment for automated acquisition, and finally (3) analysis of NETosis using the readily available image analysis software Fiji (ImageJ2). This protocol can be adapted to evaluate NETosis after different stimuli, and can be easily modified to allow high‐throughput acquisition and analysis using a multi‐well plate format. Published 2021. This article is a U.S. Government work and is in the public domain in the USA. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Neutrophil isolation and plate setup Basic Protocol 2 : Microscope and acquisition setup for automated high throughput imaging Basic Protocol 3 : Analysis of NETosis and apoptosis data